2022
DOI: 10.1155/2022/7847011
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Skin Wound Healing for Diabetic Mice with Thermosensitive Hydrogel Combined with Insulin Injection

Abstract: Chronic skin wound caused by diabetic disease is very common worldwide. Moreover, there is a shortage of effective curing technology in clinic. In this work, we developed a novel technology using thermosensitive hydrogel on wound top combined with insulin injection. The efficiency and mechanism of this technology were investigated in a diabetic mouse model. Dorsal-paired 8–10 mm diameter wounds were created in 12 mice. The wound healing rate was determined over a 28-day interval in healthy control (Control), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“… 180 A previous study reported that a thermosensitive hydrogel combined with insulin injection improved skin wound healing in diabetic mice. 181 Poloxamer 407 is widely employed for drug delivery because it is reported to be nontoxic and can form gels at 25 °C. Poloxamer 407 and insulin were injected into the wounds of diabetic mice and compared with those of other controls to measure the rate of wound healing at 28 days intervals ( Fig.…”
Section: Thermosensitive Hydrogel For Diverse Woundsmentioning
confidence: 99%
“… 180 A previous study reported that a thermosensitive hydrogel combined with insulin injection improved skin wound healing in diabetic mice. 181 Poloxamer 407 is widely employed for drug delivery because it is reported to be nontoxic and can form gels at 25 °C. Poloxamer 407 and insulin were injected into the wounds of diabetic mice and compared with those of other controls to measure the rate of wound healing at 28 days intervals ( Fig.…”
Section: Thermosensitive Hydrogel For Diverse Woundsmentioning
confidence: 99%
“…The large number of hairs induces important changes in the physiology of the skin but most importantly, healing occurs by contraction of the dermis rather than by reepithelialization of the epidermis like in humans (Pound et al, 2014). Furthermore, rodents have a much higher regenerative capacity than humans, which makes it very difficult to obtain a diabetic ulcer that does not close, even in diabetic mice (Fang et al, 2022). Another option to study diabetic ulcer is 2D cell culture models.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Insulin and its derivatives as insulin like growth factor-1 stimulate proliferation of the keratinocytes at the donor site, and increase the production of transforming growth factor beta (TGF-β), which in turn accelerates the migration of the epithelial cells to the injected area of split thickness skin graft donor site [6]. Moreover, this effect is mediated through the PI3K-Akt-Rac1 pathway throughout insulin dependent receptors, insulin enforces the extracellular matrix and collagen synthesis by increasing the proliferation, growth and maturation of myofibroblasts with neovascularization during the proliferative phase [7].…”
Section: Introductionmentioning
confidence: 99%